1978
DOI: 10.1002/bjs.1800651014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of highly selective vagotomy on the relationship between gastric mucosal blood flow and acid secretion in man

Abstract: Previous work has shown that the duodenal ulcer population can be defined by a lower ratio between gastric mucosal blood flow and acid secretion (during pentagastrin stimulation) than is found in normal subjects. The results of the present investigation have shown that the ratio is restored to normality by highly selective vagotomy. This suggests that increased tonic activity of the vagus on the parietal cell is one of the important disorders in duodenal ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…This was again observed 2 months after the operation when betazole stimulated gastric mucosal blood flow without stimulating a corresponding increase in acid secretion. Similar studies have been done in man by Knight et al [1] who also found the different effects of highly selective vagotomy on gastric mucosal blood flow and acid secretion. These investigators showed that patients with duodenal ulcer disease had a lower ratio between gastric mucosal blood flow and acid secretion (during pentagastrin stimulation) than was found in normal subjects.…”
Section: Invited Commentarysupporting
confidence: 82%
“…This was again observed 2 months after the operation when betazole stimulated gastric mucosal blood flow without stimulating a corresponding increase in acid secretion. Similar studies have been done in man by Knight et al [1] who also found the different effects of highly selective vagotomy on gastric mucosal blood flow and acid secretion. These investigators showed that patients with duodenal ulcer disease had a lower ratio between gastric mucosal blood flow and acid secretion (during pentagastrin stimulation) than was found in normal subjects.…”
Section: Invited Commentarysupporting
confidence: 82%
“…In addition to these factors, there are others that may play a part in the genesis of these lesions; some are genetic, such as increased serum pepsinogen I [2] and some are environmental, such as smoking or alcohol ingestion [2]. In our previously reported studies, we have shown that 2 elements, acid and blood flow, are clearly related in the normal stomach and that this association is different in duodenal ulcer [4] but returns to normal after highly selective vagotomy [5].…”
mentioning
confidence: 99%
“…[12][13][14] The following limitations of the method must be taken 16 neutral red, like aminopyrine, initially accumulates in the parietal cells and is consecutively washed out into the gastric lumen by the acid secretion. This explains the initial decline of the neutral red concentration in the gastric juice and the corresponding behaviour of the clearance and the R-value (Fig.…”
Section: Discussionmentioning
confidence: 99%